2020
DOI: 10.3389/fmicb.2020.01970
|View full text |Cite
|
Sign up to set email alerts
|

The First Mitochondrial Genome for Geastrales (Sphaerobolus stellatus) Reveals Intron Dynamics and Large-Scale Gene Rearrangements of Basidiomycota

Abstract: In this study, the mitogenome of artillery fungus, Sphaerobolus stellatus, was assembled and compared with other Basidiomycota mitogenomes. The Sphaerobolus stellatus mitogenome was composed of circular DNA molecules, with a total size of 152,722 bp. Accumulation of intergenic and intronic sequences contributed to the Sphaerobolus stellatus mitogenome becoming the fourth largest mitogenome among Basidiomycota. We detected large-scale gene rearrangements in Basidiomycota mitogenomes, and the Sphaerobolus stella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 69 publications
(82 reference statements)
2
15
0
Order By: Relevance
“…The phylum Basidiomycota, the largest group of mushroom-forming fungi on the earth, plays an important role in the natural circulation of forest ecosystems and people's production and life [16] , [17] . The information inferred from mitogenome analyses promoted better understanding of the origin and population genetics of Basidiomycota [18] , [19] . It has been reported that the mitogenomes of Basidiomycota vary greatly in size, genome structure, gene content, gene arrangement, repeat sequence content and intron type [20] , [21] , [22] , [23] .…”
Section: Introductionmentioning
confidence: 99%
“…The phylum Basidiomycota, the largest group of mushroom-forming fungi on the earth, plays an important role in the natural circulation of forest ecosystems and people's production and life [16] , [17] . The information inferred from mitogenome analyses promoted better understanding of the origin and population genetics of Basidiomycota [18] , [19] . It has been reported that the mitogenomes of Basidiomycota vary greatly in size, genome structure, gene content, gene arrangement, repeat sequence content and intron type [20] , [21] , [22] , [23] .…”
Section: Introductionmentioning
confidence: 99%
“…As evolution progresses, most mitochondrial genes were transferred to the nuclear genome, which was considered to have many advantages (Adams et al, 2002;Adams and Palmer, 2003). However, most fungi retain 14 conserved protein-coding genes for energy metabolism and one rps3 gene, which were called the core PCGs of the fungal mitogenome (Ye et al, 2020). In this study, these core PCGs were found to have high variation rates in the length and base composition even among the closely related species.…”
Section: Discussionmentioning
confidence: 77%
“…The dynamics of introns in Polyporales had a significant effect on Polyporales mitogenome size. The cox1 gene was found to be the largest host gene of introns in Basidiomycota 26 , 27 . In the present study, introns of Polyporales cox1 genes were classified into different position classes (Pcls) using the cox1 gene of Ganoderma calidophilum as a reference 22 , and introns belonging to the same Pcls were considered homologous introns.…”
Section: Resultsmentioning
confidence: 99%